Design of continuous flow membrane reactor for in-situ sonophotocatalytic degradation of ciprofloxacin. Issue 6 (December 2022) - Fan, Gongduan; Lin, Xin; Yang, Shangwu; Du, Banghao; Lu, Yushan; Huang, Xinyi; Wu, Jiaxin; Xu, Kai-Qin
Abstract: Antibiotics in the aquatic environments pose a severe threat to global public health. Hence, a sonophotocatalytic membrane reactor (SPMR) of sonophotocatalysis coupled membrane separation was designed to realize continuous and stable degradation of ciprofloxacin (CIP) by Bi2 MoO6 /FeVO4 in this study. The prepared catalysts were characterized by XRD, SEM, TEM, BET, UV–vis DRS, PL, and EIS. Under the optimal hydraulic retention time (HRT) of 55 min, 93.43% of CIP (10 mg/L) was degraded by Bi2 MoO6 /FeVO4 (500 mg/L) after 200 min sonophotocatalytic reaction in the presence of H2 O2 (20 mM). The synergy index (SI) of sonocatalysis and photocatalysis was calculated to 1.80 during the catalytic process. The SPMR effluent turbidity was basically nil after 10 min separation of catalyst by polyvinylidene fluoride (PVDF) hollow fiber membrane. The changes of PVDF membrane before and after use in SPMR were observed by SEM and FTIR. The membrane fouling behavior in the SPMR was investigated by membrane water flux, flux recovery rate, and membrane resistances. The mechanisms of CIP degradation are attributed to·OH and·holes (h + ) generated by Bi2 MoO6 /FeVO4 under ultrasonic and visible light irradiation. Besides, the solution matrix effects on sonophotocatalytic removal of CIP were investigated. The results proved that SPMR still maintained satisfactory sonophotocatalytic degradation efficiency in typical natural water bodies and simulated water matrices. In this work, the continuous operation process of CIP degradation and catalyst separation was realized, and the membrane fouling was alleviated by ultrasonic. Graphical Abstract: ga1 Highlights: ▪ A novel type of suspension sonophotocatalytic membrane reactor (SPMR) was designed. ▪ The reactor exhibits high performance for degrading ciprofloxacin in continuous operation. ▪ The sonophotocatalyst can be separated by polyvinylidene fluoride hollow fiber membrane. ▪ The ultrasonic alleviates membrane fouling in SPMR. ▪ The mechanisms of ciprofloxacin degradation under ultrasonic and visible light were proposed.